Designing an Energy-efficient Prototype Vehicle by the Mandalika Desantara Racing Team - Tira, Hendry Sakke; Nuarsa, I Made; Renaldy, Renaldy (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
In order to participate in the international fuel-efficient vehicle competition, a team from the Mechanical Engineering department of Mataram University has prepared a prototype vehicle. The competition is The Shell Eco-Marathon, held at the International Pertamina Mandalika Circuit in Lombok in July 2023 and attended by several teams from abroad. For this purpose, the team has developed an energy-efficient prototype vehicle using a two-wheeler engine. The team has modified the two-wheeler engine to achieve more fuel-efficient consumption compared to conventional vehicles. The study involves checking the two-wheeler engine's condition, conducting engine startup experiments, and analyzing engine performance. The Mandalika Desantara racing team reduced the piston diameter to minimize the combustion chamber volume. The results of the engine modification on the prototype vehicle show a fuel consumption rate of 71.66 km/l when driving on the Mandalika circuit. However, this figure has not yet reached the desired level of efficiency, considering that the estimated fuel consumption of vehicles with conventional motor engines is around 40-50 km/l.